Reinventing crediting for competency-based education the mastery transcript consortium model and beyond - Martin, Jonathan E. (Eye on education, 2020)
Many argue that the conventional high school transcript has become irrelevant to today's best practices in teaching, learning, and assessment. With more and more school leaders turning to alternate, competency-based approaches for learning, crediting and transcripts can follow suit by drawing on badging, micro-crediting, digital portfolios of student work, and other emerging tools. Reinventing Crediting for Competency-Based Education explores the need for this transformation while detailing the implementation of promising models, particularly the Mastery Transcript Consortium. Written by an experienced consultant and former school leader, this book will assist school and district administrators in making a forward-thinking crediting and transcript system work for their students' futures